2018
DOI: 10.1194/jlr.m080440
|View full text |Cite
|
Sign up to set email alerts
|

25-Hydroxycholesterol activates the expression of cholesterol 25-hydroxylase in an LXR-dependent mechanism

Abstract: Cholesterol 25-hydroxylase (CH25H) catalyzes the production of , an oxysterol which can play an important role in different biological processes.However, the mechanisms regulating CH25H expression have not been fully elucidated. In this study, we determined that CH25H is highly expressed in mouse liver and peritoneal macrophages. We identified several liver X receptor (LXR) response elements (LXREs) in the human CH25H promoter. In HepG2 cells, activation of LXR by 25-HC or other oxysterols and synthetic ligand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 32 publications
4
52
0
Order By: Relevance
“…In addition, CH25H is an IFN-inducible molecule (4,5). Interestingly, we have reported that expression of hepatic CH25H or macrophage IFN- can be activated by LXR (15,16). Based on the above studies, we hypothesized that LXR activation may play an important role in antiviral infection by activating CH25H expression.…”
Section: Lxr Activation Inhibits Infection Of Hsv-1 or Mlv-(vsv)-gfp mentioning
confidence: 95%
See 2 more Smart Citations
“…In addition, CH25H is an IFN-inducible molecule (4,5). Interestingly, we have reported that expression of hepatic CH25H or macrophage IFN- can be activated by LXR (15,16). Based on the above studies, we hypothesized that LXR activation may play an important role in antiviral infection by activating CH25H expression.…”
Section: Lxr Activation Inhibits Infection Of Hsv-1 or Mlv-(vsv)-gfp mentioning
confidence: 95%
“…After treatment, cellular proteins were extracted. Expression of CH25H, LXR, LXR, IFN-, SULT2B1b protein, and total HSV-1 proteins in cellular lysate was determined by Western blot as described (15). Expression of GAPDH or -tubulin was determined as loading control.…”
Section: Western Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Liu et al. reported that 25‐HC induces expression of CH25H via activation of LXR . Hence, a widely used potent LXR agonist, TO901317 was used to explore whether it could lower VLCFA levels.…”
Section: Figurementioning
confidence: 99%
“…[21] Recently, Liu et al reported that 25-HC induces expression of CH25H via activation of LXR. [22] Hence, a widely used potent LXR agonist, TO901317 was used to explore whether it could lower VLCFA levels. As shown in Figure 5, TO901317 significantly reduced VLCFA levels in CCALD and AMN fibroblasts.…”
Section: Exogenous Addition Of 25-hydroxycholesterol Reduces Level Ofmentioning
confidence: 99%